2013
DOI: 10.3171/2013.4.spine12876
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the surgical management of spine trauma in the morbidly obese patient: a case series

Abstract: Object The treatment of morbidly obese individuals with spine trauma presents unique challenges to spine surgeons and trauma staff. This study aims to increase awareness of current limitations in the surgical management of spine trauma in morbidly obese individuals, and to illustrate practical solutions. Methods Six morbidly obese patients were treated surgically for spine trauma over a 2-year period at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Increasingly, changes to care environments are being needed to accommodate larger body sizes, requiring adjustments such as widened doorways, reinforced floors, suitable seats, and larger rooms. Problems featured in the health literature demonstrate the scope of challenges, such as evacuation planning, diagnostic scanning, and positioning during surgery in theatre . Documented requirements include staff training, specialist equipment provision, and development of specialist clinical protocols covering essential areas, such as tissue viability guidance .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly, changes to care environments are being needed to accommodate larger body sizes, requiring adjustments such as widened doorways, reinforced floors, suitable seats, and larger rooms. Problems featured in the health literature demonstrate the scope of challenges, such as evacuation planning, diagnostic scanning, and positioning during surgery in theatre . Documented requirements include staff training, specialist equipment provision, and development of specialist clinical protocols covering essential areas, such as tissue viability guidance .…”
Section: Discussionmentioning
confidence: 99%
“…Problems featured in the health literature demonstrate the scope of challenges, such as evacuation planning, diagnostic scanning, and positioning during surgery in theatre . Documented requirements include staff training, specialist equipment provision, and development of specialist clinical protocols covering essential areas, such as tissue viability guidance . However, issues are not restricted to health care but affect all aspects of life, including specialist housing, adapted workplace design, larger sized fashionable and safety clothing, and barriers to travelling .…”
Section: Discussionmentioning
confidence: 99%
“…[1128] One study (2013) observed the “Best medical and surgical care may be compromised and outcome adversely affected in morbidly obese patients with spine trauma.”[28] Their 6 morbidly obese patients, who weighed over 265 pounds, and had BMIs of over 40 (range: 47.8–67.1), sustained high-speed injuries following motor vehicle accidents (MVA). Morbid obesity contributed to longer surgery, poorly fitting orthotics, suboptimal magnetic resonance (MR)/computed tomography (CT)/X-ray images including intraoperative radiographs risking wrong level surgery.…”
Section: Review Does Not Include Analysis Of Traumatic Injuries In Momentioning
confidence: 99%
“…Currently, there is in excess of 6000 outpatient centres in operation in the USA (16). The literature is satiated with data on the epidemiology and outcomes of spine operation in a hospital-based setting (17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%